2005
DOI: 10.1554/04-722
|View full text |Cite
|
Sign up to set email alerts
|

Genealogical Footprints of Speciation Processes in Wild Tomatoes: Demography and Evidence for Historical Gene Flow

Abstract: Multilocus studies assessing patterns of nucleotide polymorphism within and among closely related species provide access to genealogical information bearing on demographic and geographic aspects of their speciation history. However, the technical difficulties in obtaining sufficient sequence data have severely limited this approach thus far, especially in outbred plant taxa. We employ the analytical framework of divergence population genetics in testing the isolation model of speciation in three self-incompati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
48
1

Year Published

2008
2008
2012
2012

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 34 publications
(54 citation statements)
references
References 67 publications
(67 reference statements)
5
48
1
Order By: Relevance
“…For heterozygotes, a dual approach of both cloning before sequencing and direct sequencing was used to obtain the sequences of both alleles. As before, we developed a series of allelespecific sequencing primers whose 3 0 -end was anchored on identified SNPs or indels (for details of this approach, see Städler et al, 2005). Haplotype phase was thus completely resolved for all sequences.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For heterozygotes, a dual approach of both cloning before sequencing and direct sequencing was used to obtain the sequences of both alleles. As before, we developed a series of allelespecific sequencing primers whose 3 0 -end was anchored on identified SNPs or indels (for details of this approach, see Städler et al, 2005). Haplotype phase was thus completely resolved for all sequences.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, this study also analyzes our previously published sequences sampled from each of four populations in both S. peruvianum and S. chilense, as well as outgroup sequences from tomato relatives (Baudry et al, 2001;Roselius et al, 2005;Arunyawat et al, 2007). We also included one previously sequenced sample of S. habrochaites, which was obtained from the Tomato Genetics Resource Center at UC Davis (http://tgrc.ucdavis.edu; accession LA1775, 'Ancash', see Supplementary Table S1 and Städler et al, 2005).…”
Section: Methodsmentioning
confidence: 99%
“…Similar allele pairs across species could be a result of recently shared evolutionary history (Lu, 2001;Sutherland et al, 2008) or introgression among species (for example, Castric et al, 2008). Solanum peruvianum and S. chilense are certainly recently diverged (p0.55 million years, Städler et al, 2008), and analyses of multilocus sequence data suggest historical introgression (Städler et al, 2005(Städler et al, , 2008. Castric et al, 2008 reported sets of similar alleles at the SRK (S-locus receptor kinase) pistil SI specificity determining gene in Arabidopsis lyrata and A. halleri (Brassicaceae) and demonstrated that levels of introgression at SRK were higher than background levels.…”
Section: Js Miller and Jl Kostyunmentioning
confidence: 99%
“…Self-incompatible (SI) wild tomato species yielded higher estimates of diversity, for example, Solanum habrochaites S Knaap and DM Spooner (one accession), Solanum chilense (Dunal) Reiche (four populations) and S. peruvianum (four populations). Differences observed among wild tomato species in mean diversity have arisen through a variety of factors including mating system, demography and population structure (Baudry et al, 2001;Roselius et al, 2005;Städler et al, 2005;Arunyawat et al, 2007).…”
Section: Diversity Estimatesmentioning
confidence: 99%
“…Historical or recent gene flow among wild tomato species (Nesbitt and Tanksley, 2002;Städler et al, 2005;Arunyawat et al, 2007) and between wild species and the cultivar imposes challenges for evolutionary studies. Notably, a Mexican versus a South American domestication origin continues to be debated Peralta and Spooner, 2007).…”
Section: Introgressionmentioning
confidence: 99%